Review of the genus Trichoboscis Meyrick, with descriptions of three new species (Lepidoptera, Lecithoceridae) - Park, Kyu-Tek; Liu, Shurong; Heppner, John B.; Pathania, Prakash. C.; Wang, Shuxia (Zootaxa, 2015)
Trichoboscis Meyrick belongs to the subfamily Lecithocerinae of Lecithoceridae. It is a small, poorly known genus, comprising two known species described from India. In this study, three new species are described: T. multispina Park & Wang, sp. nov. and T. phliuensis Park & Wang, sp. nov. from Thailand, and T. cultriformis Park & Wang, sp. nov. from China. Images of adults and genitalia are provided, along with a key to all the described species in the genus.